Description of the first species of Gonadryinus Olmi (Hymenoptera, Dryinidae) from the Afrotropical region - Guglielmino, Adalgisa; Olmi, Massimo; Marletta, Alessandro; Speranza, Stefano (Zootaxa, 2017)
Gonadryinus bicarinatus Olmi, Marletta, Guglielmino & Speranza, sp. nov., from Ranomafana National Park (Fianarantsoa Province, Madagascar) is described and illustrated. This represents the first record of Gonadryinus from the Afrotropical region. The genus was previously known only from the Neotropical region, where only one species, G. hansoni Olmi, 1991, is recorded. The new taxon is different from G. hansoni because of the palpal formula 5/3 (4/2 in G. hansoni), the occipital carina complete (incomplete in G. hansoni) and two longitudinal keels present on the dorsal surface of the metapectal-propodeal complex (no longitudinal keels in G. hansoni).